2014
DOI: 10.1542/peds.2013-3102
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Rates After Intussusception Enema Reduction: A Meta-analysis

Abstract: BACKGROUND AND OBJECTIVE: Reported rates of recurrence after enema reduction for intussusception are variable. Concerns for recurrence influence postreduction management. The objective of this study was to conduct a systematic review and meta-analysis to estimate overall, 24-hour, and 48-hour recurrence rates after enema reduction in children.METHODS: PubMed, Cochrane Database, and OVID Medline were searched from 1946 through December 2011 using the search terms: intussusception, recurrence, and enema. Sixty-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 69 publications
4
39
3
5
Order By: Relevance
“…A 2014 meta-analysis (based on 69 studies) estimated the rate of recurrence for fluoroscopy guided enema to be 8.5% (95% CI = 6.9% to 10.4%) with 26% of these occurring within 24 hours and 32% within the first 48 hours. 19 Based on this low rate of recurrence in the immediate postreduction period, the investigators of the meta-analysis concluded that well-appearing patients can be safely discharged home from the ED. In the current study, we noted an overall recurrence rate of 5.6% within 1 week, with approximately 50% of the repeat enema reductions occurring within 18 hours after the initial reduction.…”
Section: Discussionmentioning
confidence: 99%
“…A 2014 meta-analysis (based on 69 studies) estimated the rate of recurrence for fluoroscopy guided enema to be 8.5% (95% CI = 6.9% to 10.4%) with 26% of these occurring within 24 hours and 32% within the first 48 hours. 19 Based on this low rate of recurrence in the immediate postreduction period, the investigators of the meta-analysis concluded that well-appearing patients can be safely discharged home from the ED. In the current study, we noted an overall recurrence rate of 5.6% within 1 week, with approximately 50% of the repeat enema reductions occurring within 18 hours after the initial reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography has been widely adopted to screen and diagnose Intussusception is more likely to recur after nonoperational reduction [3]. Overall recurrence rates after pneumatic enema was around 7.9-8.5 % as previously reported [2,4,5], among them, approximately one-third were early recurrences within 72 h after the reduction [5]. Previous studies have failed to identify consistent risk factors for intussusception recurrence and the characteristic of early recurrence are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nonoperatif redüksiyonlarda nüksün az görüldüğü (%3-6) ve nükslerinde büyük bir çoğunluğunun 24-48 saat içinde gerçekleştiği bildirilmiştir (10,14) . Bu nedenle olgular redüksiyon sonrası bir gün daha klinikte gözlenmiş ve çıkmadan önce birkez daha US ile kontrol edilmiştir.…”
Section: Discussionunclassified